ANÁLISE DO NÍVEL DE EFICIÊNCIA ENERGÉTICA DE UMA HABITAÇÃO EM WOOD FRAME PELOS MÉTODOS PRESCRITIVO E SIMULAÇÃO DO RTQ-R - Zara, Rafaela Benan; Santos, Vanessa Costa; Giglio, Thalita Gorban Ferreira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Technical Regulation for Quality of Energy Efficiency Level of Residential Building (RTQ-R) allows to evaluate the thermo-energy performance of dwellings by means of two methods: the prescriptive and the computational simulation. This work aims analysis the energy efficiency of a wood frame building, applying both methods, in order to analyze a measurement capacity in the equation of the prescriptive method. Thus, the performance of dwellings with variation of five panels and coverage was evaluated. The analyzes were performed using the EnergyPlus software and the performance sheet provided by the Brazilian Labeling Program (PBE Edifica) for the Bioclimatic Zone 3, represented by the city of São Paulo. The results showed differences of one to two levels in the energy efficiency classification and the prescriptive method presented highest thermal performance indicators. Although the results by simulation showed the good performance of the panels with insulation insertion, by the prescriptive method there were no performance differences related to low thermal capacity and low thermal transmittance.